Flow Unit Model of Channel Sand Body and Its Effect on Remnant Oil Distribution: A Case Study of PI Formation in the Eastern Transition Zone of Daqing Oilfield - Yue Zhang; You-liang Ji; Hui-jian Wen; Shi-zhong Ma; Dong-lai Bai; Bin-chi Zhang; Ben-kang Xing (Geofluids)
To analyze the effect of various flow units in a channel sand body on remnant oil, we established a connection between various flow unit types and the remnant oil distribution. Using stratigraphic correlation and the characterization of sedimentary microfacies, we describe a single sand body, point bar, and narrow channel located at the injection-production well pattern of well B2-60-FB271 in the Eastern transition zone of the Daqing Placanticline. Architecture models of the point bar and narrow channel are also established using a series of parameters from different measurement methods. Four types of flow units (strong-current limiting, medium-current limiting, weak-current limiting, and none-current limiting) in the point bar sand body were identified, whereas one type, unshielded unit, was identified in the narrow channel. Geological parameters, such as porosity, permeability, and pore-throat radius (r50), were optimized to quantitatively characterize these various flow units. Samples were obtained from well B2-60-FB271 and analyzed by the freeze-fluorescence thin section technique. According to the displacement degree, the microscopic remnant oil was divided into three types: (1) free-state remnant oil, (2) semi-free-state remnant oil, and (3) bound-state remnant oil. We found that the strong-current limiting flow unit in the point bar is the enrichment area of free-state microscopic remnant oil and that the medium-current limiting and weak-current limiting flow units also have relatively high free microscopic remnant oil. These constitute the remaining oil enrichment areas in the study area.